2012
DOI: 10.3746/jkfn.2012.41.8.1029
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Extract Fractions of Leaves from Loquat (Eriobotrya japonica Lindl.) by Cultivars

Abstract: In this study, we compared the antioxidant activities of three loquat (Eriobotrya japonica Lindl.) by cultivars (Daebang, Bubang and native cultivar). The leaves were extracted by 80% ethanol and then fractionated with various solvents (n-hexane, ethyl acetate, n-butanol, and water) for biological activities and bioactive compounds analysis. Total polyphenol content of extracts and fractions was in the range of 84.93~478.50 mg/g gallic acid equivalent (GAE). From highest to lowest GAE, the fractions were n-but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Also, this plant has been reported to have anti-inflammatory, antioxidant and antiviral effects (Bucak et al, 2019;Naveed et al, 2018). Especially, chlorogenic acid, cryptochlorogenic acid, neochlorogenic acid has been focused on regulate fat metabolism and glucose with antioxidant activity and various physiological activities (Khanduja et al, 1999;Lee et al, 2004;Shin et al, 2012;Naveed et al, 2018). The current study was developed a method for the extraction, isolation, and identification of three phenolic compounds from E. japonica leaves.…”
Section: Application Of the Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, this plant has been reported to have anti-inflammatory, antioxidant and antiviral effects (Bucak et al, 2019;Naveed et al, 2018). Especially, chlorogenic acid, cryptochlorogenic acid, neochlorogenic acid has been focused on regulate fat metabolism and glucose with antioxidant activity and various physiological activities (Khanduja et al, 1999;Lee et al, 2004;Shin et al, 2012;Naveed et al, 2018). The current study was developed a method for the extraction, isolation, and identification of three phenolic compounds from E. japonica leaves.…”
Section: Application Of the Methodsmentioning
confidence: 97%
“…Especially, the leaves of E. japonica have been widely used as a traditional medicine with beneficial effects as an expectorant, for hemoptysis, quenching thirst, chronic bronchitis, edema, septic settlement, and a strong stomach (Shin et al, 2012). According to recent study, it has been reported to be the effect of various component analyses (Bae et al, 2002;Bae et al, 2005), gastroenteritis improvement (Takuma et al, 2008), antioxidant (Hwang et al, 2010;Park et al, 2008;Jeong et al, 2009), anticancer (Kim et al, 2009c;Lee et al, 2004), antibacterial (Bae et al, 2002;Bae et al, 2005;, anti-inflammatory (Shin et al, 2012;Kim et al, 2009a;Banno et al, 2005), anti-diabetic (Kim et al, 2009b;Kim et al, 2006;Chen et al, 2008), skin whitening and skin allergy inhibition (Sun et al, 2007). Also, it has garnered attention in various herbal ingredients markets because it is safe and does not have side effects (Hwang et al, 2010;Lee et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is grown mainly in mild climatic conditions such as Jeju, Gyeongnam and Jeonnam in Korea (Park & Park, 1995;Park & Kim, 2000). It has been known in traditional medicines that E. japonica fruits and leaves are effective for antitussives, expectorant, vomiting, hemoptysis, and diuresis, and are also reported to be effective in relieving breathing and thirst (Eom et al, 2009;Shin et al, 2012;Lee et al, 2016a). The E. japonica leaves contains a large amount of bioactive compounds such as terpenoid-based compounds (ursolic acid, oleanolic acid etc.)…”
mentioning
confidence: 99%